ANALYSIS OF HUMAN RESOURCE NEEDS IN THE MEDICAL RECORDS UNIT IN RSU MITRA MEDIKA BANDAR KLIPPA USING THE HEALTH WORKLOAD ANALYSIS METHOD: HUMAN RESOURCE NEEDS - Ode, Anggun Nabila; Putri, Dea Hamiche; Vilasari, Dwi; Purba, Rahmadani; Sahilla, Rizka; Simangunsong, Rizky Aulia; Harahap, Sinta Pretti (STIKes Mandala Waluya Kendari, 2025)
Background: This research aims to help RSU Mitra Medika Bandar Klippa better organize and manage its human resources in order to deliver high-quality healthcare services. The aim of this study is to electronically manage and retain patient health data so that the medical staff can promptly and accurately access information, while some healthcare facilities are still having trouble integrating electronic medical records. Methods: The research used descriptive method with a case study approach, which tries to provide a detailed and in-depth description of events that occur in a particular analysis unit. Results: The research used descriptive method with a case study approach, which tries to provide a detailed and in-depth description of events that occur in a particular analysis unit. Conclusion: One of the study's recommendations is for present medical professionals to get education to enhance their skills and increase job prospects based on the needs analysis. Additionally, the RSU Mitra Medika Bandar Kalipa should have seven staff.